2020
DOI: 10.1364/boe.387254
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral image quality in pseudophakic eyes

Abstract: The purpose of this work was to evaluate peripheral image quality in the pseudophakic eye using computational, physical, and psychophysical methods. We designed and constructed a physical model of the pseudophakic human eye with realistic dimensions using a corneal phantom and a board-only camera that was pivoted around an axis that matched the anatomical center of a human retina, assuming a radius of curvature of 12 mm, while it was submersed in a 23.4 mm long water filled chamber to emulate human ocular axia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…When a thin IOL replaces the thick natural lens, the pseudophakic eye introduces high amounts of astigmatism compared to the natural eye. Psychophysical tests have show that the astigmatism could reduce visual field sensitivity in the peripheral vision [4] . Further, in the case of detection and low-contrast resolution, degradation of optical performance has an impact on the peripheral vision which reduce the pseudophakic patient's performance in some daily visual tasks [5] .…”
Section: Introductionmentioning
confidence: 99%
“…When a thin IOL replaces the thick natural lens, the pseudophakic eye introduces high amounts of astigmatism compared to the natural eye. Psychophysical tests have show that the astigmatism could reduce visual field sensitivity in the peripheral vision [4] . Further, in the case of detection and low-contrast resolution, degradation of optical performance has an impact on the peripheral vision which reduce the pseudophakic patient's performance in some daily visual tasks [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Intraocular lenses (IOLs) used in cataract surgery have been primarily designed as thin lenses to simplify surgical technique, resulting in increased peripheral astigmatism compared to the natural crystalline lens of the eye [ 7 ]. A recent study has shown that standard monofocal IOLs, commonly used in cataract surgery, can cause a decrease in the detection threshold in the far periphery [ 8 ] and the use of IOLs designed to improve peripheral image quality can increase peripheral field sensitivity [ 9 ]. Additionally, recent research shows a significant field distortion in the pseudophakic eye [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…revious clinical studies and computational modeling have shown that the retinal image in the peripheral visual field differs in pseudophakic eyes than in phakic eyes. [1][2][3][4][5][6][7][8] Recent studies found that the peripheral retinal image quality is degraded in pseudophakic patients and peripheral image degradation can affect visual function. 1,9 Reduced contrast and image quality in the periphery of the visual field could also affect diagnostic and imaging procedures in pseudophakic eyes, such as wide-field retinal imaging or visual field testing.…”
mentioning
confidence: 99%
“…Experimental studies on physical model eyes that incorporate IOLs can help validate simulations and study the peripheral behavior of lenses. 5 A limitation of artificial eye models is that the peripheral behavior is determined by the combined contribution of the artificial cornea and the IOL. A more specific understanding of the impact of IOL design parameters such as lens shape and asphericity on peripheral optical performance can be gained by quantifying the peripheral behavior of the isolated IOL.…”
mentioning
confidence: 99%